Aluminum-doped modified mixed sodium ferric phosphate positive electrode material and preparation method thereof
By mixing AL3+in the positive electrode material of sodium ions, prepare aluminum mixing and modified mixed sodium phosphate orthopedic materials, solve the problem of low theoretical capacity of existing materials and poor circulation stability, and achieve high capacity, excellent circulation, excellent circulation Stability and high -power performance.
Patent Information
- Application Number
- CN202411569375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing sodium ion battery positive electrode materials have low theoretical capacity during the charge and discharge cycle, and have poor cycle stability and rate performance, making it difficult to meet the requirements of large-scale commercial applications.
Through the solution-gel method, AL3+doped into NAFEPO4, prepare aluminum mixed mixed mixed sodium phosphate na4.4fe3.4AL0.1 (PO4) 2.5 (P2O7)/C, and obtain carbon carbon through high temperature roasting Covering materials improve their electronic conductivity and structural stability.
It significantly improves the diffusion kinetics and conductivity of Na+, improves the initial capacity and cycle stability of the material, exhibits high rate performance, and has good cycle stability even at high current densities.
Smart Images

Figure CN119361653A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an aluminum-doped modified mixed sodium iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] Sodium-ion batteries (SIBs) have abundant Na + The availability of raw materials and the similar electrochemical performance of SIBs and lithium-ion batteries (LIBs) have attracted great research and development interest in the field of grid-scale energy storage systems (ESS). However, it is still a huge challenge to obtain Na-ion battery cathode materials with both excellent electrochemical performance and good cost-effectiveness while meeting the requirements of ESS.
[0003] Given the commercial success of LiFePO4 cathode materials in lithium-ion batteries, benign and inexpensive iron-based phosphates with similar properties are considered to be one of the best choices for polyanion cathode materials for sodium-ion batteries. However, due to the special thermodynamic properties of olivine-phase NaFePO4 (NFP), phosphite-phase NaFePO4 is often obtained in the traditional synthesis process, so the expected olivine-phase NaFePO4 cannot be obtained by conventional methods. Due to the lack of effective Na + Ion diffusion channel, it is generally believed that the sodium ferrophosphate phase NaFePO4 is not electrochemically active. Fortunately, Na2FeP2O7 derived from NaFePO4 can be directly synthesized by simple methods such as mechanical synthesis and sol-gel method, with low cost. And because the lattice is basically not distorted during the charge and discharge process, it has strong cycle performance and good structural stability. Although Na2FeP2O7 shows an open three-dimensional Na + channel and allow a higher operating voltage (~3.0 V), but this cathode material can only pass one sodium ion during the charge-discharge cycle, resulting in a low theoretical capacity of 97.1 mAh g -1 , which hinders its large-scale commercial application. In this regard, polyanionic phosphates composed of NaFePO4 and Na2FeP2O7 in a 1:1 molar ratio have attracted extensive research interest. This mixed phosphate compound combines the advantages of phosphate and pyrophosphate cathodes, thus having good electrochemical performance. Na4Fe3(PO4)2(P2O7) (NFPP) (orthorhombic Pn21a) can achieve a higher theoretical capacity (~129 mAh g) at an average voltage of 3.0 V. -1). Doping is an effective way to improve the electronic conductivity of materials. It can introduce impurity energy levels and improve structural stability by introducing inert ions. Therefore, it is of great significance to develop a doped NaFePO4 with high specific capacity, excellent cycle stability and rate performance as a positive electrode material for sodium ion batteries. Summary of the invention
[0004] In view of the above deficiencies in the prior art, the present invention provides an aluminum-doped modified mixed sodium iron phosphate positive electrode material and a preparation method thereof. The aluminum-doped modified mixed sodium iron phosphate positive electrode material provided by the present invention has a high specific capacity, excellent cycle stability and rate performance, and has good cycle stability even at high current density.
[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0006] In the first aspect, the present invention provides an aluminum-doped modified mixed sodium iron phosphate positive electrode material, the chemical formula of which is Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C.
[0007] Preferably, the aluminum-doped modified mixed sodium iron phosphate positive electrode material is prepared by a sol-gel method. 3+ After being doped into NFPP, it is obtained by high-temperature calcination.
[0008] The aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C has excellent electronic conductivity and structural stability, and Na + The diffusion kinetics and conductivity of the aluminum-doped modified mixed sodium iron phosphate cathode material are significantly improved; in addition, the aluminum-doped modified mixed sodium iron phosphate cathode material has a high initial capacity and exhibits very excellent cycle stability and high rate performance. 3+ The carbon-coated aluminum-doped modified mixed sodium iron phosphate cathode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C; among them, aluminum doped transition metal sites replace part of the iron atoms. 3+ The radius is small, and aluminum doping will produce Na + and Fe 2+ vacancies, thereby improving the electronic conductivity; in addition, the inactive Al 3+Not participating in the redox reaction can reduce the change in crystal volume and prevent the collapse of the crystal structure during charge and discharge cycles, thereby improving the cycle stability.
[0009] In a second aspect, the present invention provides a method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material, comprising the following steps:
[0010] S1. The iron source and the sodium source are dissolved in water according to a molar ratio and mixed to obtain a solution M1;
[0011] S2. The phosphorus source and the aluminum source were added to the solution M1 according to a molar ratio and mixed to obtain a solution M2;
[0012] S3. The carbon source is added to solution M2 and mixed to obtain solution M3;
[0013] S4. The solution M3 is heated to form a wet gel;
[0014] S5. vacuum drying the wet gel to obtain a dry gel;
[0015] S6. Grind the dry gel to obtain a powder precursor, pre-sinter and calcine the powder precursor under an inert atmosphere, and then cool to room temperature to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material.
[0016] The aluminum-doped modified mixed sodium iron phosphate positive electrode material of the present invention is prepared by a sol-gel method and subsequent high-temperature calcination. In the steps, an iron source and a sodium source are first added to be uniformly dissolved under stirring; then a phosphorus source and an aluminum source are added, and stirring is maintained at room temperature to form a Na 4.5-x Fe 3.5-x Al x (PO4) 2.5 (P2O7); then add a carbon source, mix well, and evaporate the water by heating and stirring to obtain a wet gel; further heat and evaporate the water in the wet gel to obtain a dry gel; grind the dry gel into powder, and calcine it at high temperature under the protection of inert gas to obtain Na 4.5-x Fe 3.5-x Al x (PO4) 2.5 (P2O7) / C.
[0017] Preferably, in step S1, the molar ratio of the iron source to the sodium source is 3.4:4.4.
[0018] Preferably, in step S1, the mixing time is 30-60 min, and the mixing temperature is 20-25 °C.
[0019] Preferably, in step S1, the iron source includes a mixture of one or more of ferric nitrate nonahydrate, ferrous oxalate, and ferrous sulfate; the sodium source includes a mixture of one or more of sodium fluoride, sodium acetate, sodium carbonate, and sodium nitrate.
[0020] Preferably, in step S2, the molar ratio of the phosphorus source to the aluminum source is 4.5:0.1.
[0021] Preferably, in step S2, the phosphorus source includes a mixture of one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium dihydrogen phosphate; the aluminum source includes a mixture of one or more of aluminum nitrate nonahydrate, aluminum sulfate, and aluminum chloride.
[0022] Preferably, in step S3, the mass of the carbon source is 20% of the total mass of the iron source, the sodium source, the phosphorus source and the aluminum source.
[0023] Preferably, in step S3, the carbon source comprises a mixture of one or more of citric acid, oxalic acid and glucose.
[0024] Preferably, in step S4, the heating temperature is 70-90°C.
[0025] Preferably, in step S5, the vacuum drying is carried out at a temperature of 100-120° C. and for a time of 10-12 h.
[0026] Preferably, in step S6, the inert atmosphere is argon or nitrogen.
[0027] Preferably, in step S6, the pre-firing temperature is 300-400° C. and the time is 2-5 h.
[0028] Preferably, in step S6, the calcination temperature is 500-600° C. and the calcination time is 5-10 h.
[0029] In a third aspect, the present invention provides the use of the aluminum-doped modified mixed sodium iron phosphate positive electrode material or the aluminum-doped modified mixed sodium iron phosphate positive electrode material prepared by the method in preparing a positive electrode for a sodium ion battery.
[0030] Compared with the prior art, the present invention is beneficial in that:
[0031] (1) The aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C has excellent electronic conductivity and structural stability, and Na +The diffusion kinetics and conductivity are significantly improved; in addition, the aluminum-doped modified mixed sodium iron phosphate positive electrode material has a high initial capacity and exhibits very excellent cycle stability and high rate performance.
[0032] (2) The aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 The current density of (P2O7) / C at 0.2C can reach 133 mAh·g -1 The reversible capacity has a capacity retention rate of 99% after 500 cycles at a current density of 20C; and a capacity retention rate of 88% after 2500 cycles at a high current density of 50C. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 XRD pattern of (P2O7) / C;
[0034] Figure 2 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 SEM image of (P2O7) / C;
[0035] Figure 3 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 TEM image of (P2O7) / C;
[0036] Figure 4 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4)2.5 The charge-discharge curves of the first week of the (P2O7) / C charge-discharge process;
[0037] Figure 5 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 Ratio diagram of (P2O7) / C;
[0038] Figure 6 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 Cycling performance diagram of (P2O7) / C at 20C current density;
[0039] Figure 7 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 Cycling performance diagram of (P2O7) / C at 50C current density. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention provides an aluminum-doped modified mixed sodium iron phosphate positive electrode material, the chemical formula of which is Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C.
[0042] The aluminum-doped modified mixed sodium iron phosphate positive electrode material is prepared by a sol-gel method. 3+ After being doped into NFPP, it is obtained by high-temperature calcination.
[0043] The preparation method of the aluminum-doped modified mixed sodium iron phosphate positive electrode material comprises the following steps:
[0044] S1. The iron source and the sodium source are dissolved in water according to a molar ratio and mixed to obtain a solution M1;
[0045] S2. The phosphorus source and the aluminum source were added to the solution M1 according to a molar ratio and mixed to obtain a solution M2;
[0046] S3. The carbon source is added to solution M2 and mixed to obtain solution M3;
[0047] S4. The solution M3 is heated to form a wet gel;
[0048] S5. vacuum drying the wet gel to obtain a dry gel;
[0049] S6. Grind the dry gel to obtain a powder precursor, pre-sinter and calcine the powder precursor under an inert atmosphere, and then cool to room temperature to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material.
[0050] Example 1
[0051] An aluminum-doped modified mixed sodium iron phosphate positive electrode material, the preparation method is as follows:
[0052] S1. Dissolve 0.0034 mol of ferric nitrate nonahydrate in 100 mL of deionized water, stir to dissolve to obtain a clear solution, add 0.0044 mol of sodium acetate to the above solution, stir evenly at room temperature for 1 h, and obtain a clear solution M1;
[0053] S2. 0.0045 mol of ammonium dihydrogen phosphate and 0.0001 mol of aluminum nitrate nonahydrate were sequentially added to solution M1, and stirring was maintained to obtain a yellow-green solution M2;
[0054] S3. Add 20% of the total mass of the iron source, sodium source, phosphorus source and aluminum source, glucose (0.886 g) to solution M2, keep the stirring conditions unchanged and the solution color unchanged, to obtain solution M3;
[0055] S4. Place solution M3 in an 80 °C oil bath and heat with stirring until a white gel is formed;
[0056] S5. The white gel was transferred to a vacuum drying oven and dried at 120 °C for 12 h to obtain a white dry gel;
[0057] S6. The obtained white dry gel was ground with a pestle to obtain a powder precursor, which was placed in a tube furnace and pre-fired at 350 °C under the protection of an argon atmosphere for 3 h, then heated to 550 °C at a rate of 5 °C / min for calcination, and kept at this temperature for 5 h. Finally, the powder precursor was cooled to room temperature in the tube furnace to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C.Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 The XRD, SEM and TEM images of (P2O7) / C are shown in Figure 2. Figure 1 , Figure 2 , Figure 3 shown.
[0058] Comparative Example 1
[0059] A method for preparing a mixed sodium iron phosphate positive electrode material, the preparation method is as follows:
[0060] S1. Dissolve 0.0035 mol of ferric nitrate nonahydrate in 100 mL of deionized water, stir to dissolve to obtain a clear solution, add 0.0044 mol of sodium acetate to the above solution, stir evenly at room temperature for 1 h, and obtain a clear solution M1;
[0061] S2. Add 0.0045 mol of ammonium dihydrogen phosphate to solution M1, keep stirring, and obtain a yellow-green solution M2;
[0062] S3. Add 20% of the total mass of the iron source, sodium source, and phosphorus source, glucose (0.821 g), to solution M2, while keeping the stirring conditions unchanged and the color of the solution unchanged, to obtain solution M3;
[0063] S4. Place solution M3 in an 80 °C oil bath and heat with stirring until a white gel is formed;
[0064] S5. The white gel was transferred to a vacuum drying oven and dried at 120 °C for 12 h to obtain a white dry gel;
[0065] S6. The obtained white dry gel was ground with a pestle to obtain a powder precursor, which was placed in a tube furnace and pre-fired at 350 °C under the protection of argon atmosphere for 3 h, then heated to 550 °C at a rate of 5 °C / min for calcination, and kept at this temperature for 5 h. Finally, the mixed sodium iron phosphate positive electrode material Na was obtained by cooling to room temperature in the tube furnace. 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C.
[0066] Comparative Example 2
[0067] An aluminum-doped modified mixed sodium iron phosphate positive electrode material, the preparation method is as follows:
[0068] S1. Dissolve 0.00345 mol of ferric nitrate nonahydrate in 100 mL of deionized water, stir to dissolve to obtain a clear solution, add 0.00445 mol of sodium acetate to the above solution, stir evenly at room temperature for 1 h, and obtain a clear solution M1;
[0069] S2. 0.0045 mol of ammonium dihydrogen phosphate and 0.00005 mol of aluminum nitrate nonahydrate were sequentially added to solution M1, while maintaining stirring conditions, to obtain a yellow-green solution M2;
[0070] S3. Add 20% of the total mass of iron source, sodium source, phosphorus source and aluminum source, glucose (0.832 g) to solution M2, keep the stirring conditions unchanged and the solution color unchanged, to obtain solution M3;
[0071] S4. Place solution M3 in an 80 °C oil bath and heat with stirring until a white gel is formed;
[0072] S5. The white gel was transferred to a vacuum drying oven and dried at 120 °C for 12 h to obtain a white dry gel;
[0073] S6. The obtained white dry gel was ground with a pestle to obtain a powder precursor, which was placed in a tube furnace and pre-fired at 350 °C under the protection of an argon atmosphere for 3 h, then heated to 550 °C at a rate of 5 °C / min for calcination, and kept at this temperature for 5 h. Finally, the powder precursor was cooled to room temperature in the tube furnace to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material Na4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C.
[0074] Comparative Example 3
[0075] An aluminum-doped modified mixed sodium iron phosphate positive electrode material, the preparation method is as follows:
[0076] S1. Dissolve 0.00335 mol of ferric nitrate nonahydrate in 100 mL of deionized water, stir to dissolve to obtain a clear solution, add 0.00435 mol of sodium acetate to the above solution, stir evenly at room temperature for 1 h, and obtain a clear solution M1;
[0077] S2. 0.0045 mol of ammonium dihydrogen phosphate and 0.00015 mol of aluminum nitrate nonahydrate were sequentially added to solution M1, and stirring was maintained to obtain a yellow-green solution M2;
[0078] S3. Add 20% of the total mass of the iron source, sodium source, phosphorus source and aluminum source, glucose (0.853 g), to solution M2, keep the stirring conditions unchanged, and keep the color of the solution unchanged, to obtain solution M3;
[0079] S4. Place solution M3 in an 80 °C oil bath and heat with stirring until a white gel is formed;
[0080] S5. The white gel was transferred to a vacuum drying oven and dried at 120 °C for 12 h to obtain a white dry gel;
[0081] S6. The obtained white dry gel was ground with a pestle to obtain a powder precursor, which was placed in a tube furnace and pre-fired at 350 °C under the protection of an argon atmosphere for 3 h, then heated to 550 °C at a rate of 5 °C / min for calcination, and kept at this temperature for 5 h. Finally, the powder precursor was cooled to room temperature in the tube furnace to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 (P2O7) / C.
[0082] Application Examples
[0083] The positive electrode material, conductive agent (Super P), and polyvinylidene fluoride (PVDF) prepared in Example 1 and Comparative Examples 1 to 3 were mixed uniformly in a mass ratio of 7: 2: 1, dispersed in N-methyl-2-pyrrolidone (NMP) solvent to form a uniform slurry, and coated on aluminum foil using a scraper or a four-sided coater to form a positive electrode sheet. The coated aluminum foil was placed in a drying oven at 120 ° C and dried for 12 h, and then the coated aluminum foil was cut into a circular electrode sheet with a diameter of 12 mm, and placed in a glove box to assemble a button battery (CR2032). The prepared positive electrode material was used as the working electrode, and a sodium block was used as the counter electrode to test its electrochemical performance. Among them, the diaphragm used Whatman GF / A, and the electrolyte system was a solute of 1M NaClO4 and a solvent of ethylene carbonate (EC) + dimethyl carbonate (DMC) + 5% FEC, and the volume ratio of EC and DMC was 1:1.
[0084] The electrochemical performance of the assembled button battery was tested. The test instrument used for the electrochemical performance test was as follows: LANHE-CT2001A multi-channel battery test system produced by Wuhan Landian Electronics Co., Ltd., with a static time of 8 h, a voltage window range of 1.8-4.3 V, and a current density range of 20-5000 mA·g -1 , the number of cycles ranges from 100 to 3000 times.
[0085] Figure 4 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 The first cycle charge and discharge curve of (P2O7) / C charge and discharge process. Figure 4 It can be seen that the Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C has the highest specific capacity in the first week, which is 133 mA·g -1 .
[0086] Figure 5 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 (P2O7) / C ratio diagram. Figure 5 It can be seen that the Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C maintains a higher specific capacity at all current densities.
[0087] Figure 6 The Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 1 4.5 Fe 3.5 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 2 4.45 Fe 3.45 Al 0.05 (PO4) 2.5 (P2O7) / C, Na prepared in Comparative Example 3 4.35 Fe 3.35 Al 0.15 (PO4) 2.5 Cyclic performance diagram of (P2O7) / C at 20C current density. Figure 6 It can be seen that the Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C still has ultra-high capacity retention and cycle stability at a current density of 20C.
[0088] Figure 7 The Na prepared in Example 1 4.4 Fe 3.4 Al0.1 (PO4) 2.5 Cyclic performance diagram of (P2O7) / C at 50C current density. Figure 7 It can be seen that the Na prepared in Example 1 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 At a high current density of 50C, (P2O7) / C still has a high capacity retention rate of 88% after 2500 cycles.
[0089] In summary, the aluminum-doped modified mixed sodium iron phosphate positive electrode material Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C has excellent electronic conductivity and structural stability, and Na + The diffusion kinetics and conductivity are significantly improved; in addition, the aluminum-doped modified mixed sodium iron phosphate positive electrode material has a high initial capacity and exhibits very excellent cycle stability and high rate performance.
[0090] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. An aluminum-doped modified mixed sodium iron phosphate positive electrode material, characterized in that: The chemical formula is Na 4.4 Fe 3.4 Al 0.1 (PO4) 2.5 (P2O7) / C.
2. The aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 1, characterized in that: The aluminum-doped modified mixed sodium iron phosphate positive electrode material is prepared by a sol-gel method. 3+ After being doped into NFPP, it is obtained by high-temperature calcination.
3. A method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material, characterized in that: The following steps are involved: S1. The iron source and the sodium source are dissolved in water according to a molar ratio and mixed to obtain a solution M1; S2. The phosphorus source and the aluminum source were added to the solution M1 according to a molar ratio and mixed to obtain a solution M2; S3. The carbon source is added to solution M2 and mixed to obtain solution M3; S4. The solution M3 is heated to form a wet gel; S5. vacuum drying the wet gel to obtain a dry gel; S6. Grind the dry gel to obtain a powder precursor, pre-sinter and calcine the powder precursor under an inert atmosphere, and then cool to room temperature to obtain an aluminum-doped modified mixed sodium iron phosphate positive electrode material.
4. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The molar ratio of the iron source to the sodium source is 3.4:4.
4.
5. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The molar ratio of the phosphorus source to the aluminum source is 4.5:0.
1.
6. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The mass of the carbon source is 20% of the total mass of the iron source, the sodium source, the phosphorus source and the aluminum source.
7. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The iron source includes a mixture of one or more of ferric nitrate nonahydrate, ferrous oxalate, and ferrous sulfate; The sodium source includes a mixture of one or more of sodium fluoride, sodium acetate, sodium carbonate and sodium nitrate; The phosphorus source includes a mixture of one or more of diammonium phosphate, diammonium hydrogen phosphate, and sodium dihydrogen phosphate; The aluminum source includes a mixture of one or more of aluminum nitrate nonahydrate, aluminum sulfate, and aluminum chloride; The carbon source includes a mixture of one or more of citric acid, oxalic acid and glucose.
8. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The heating temperature is 70-90°C.
9. The method for preparing an aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 3, characterized in that: The pre-sintering temperature is 300-400°C, and the time is 2-5 hours; the sintering temperature is 500-600°C, and the time is 5-10 hours.
10. Use of the aluminum-doped modified mixed sodium iron phosphate positive electrode material according to claim 1 or 2, or the aluminum-doped modified mixed sodium iron phosphate positive electrode material prepared by the method according to any one of claims 3 to 9 in preparing a positive electrode for a sodium ion battery.
Citation Information
Patent Citations
Mixed crystal type polyanionic phosphate positive electrode material for sodium ion battery and preparation method of mixed crystal type polyanionic phosphate positive electrode material
CN113675390A
Sodium-rich sodium ferric pyrophosphate positive electrode material, preparation method and application
CN116119642A
Sodium-rich sodium ferric phosphate positive electrode material and preparation method and application thereof
CN116332144A
Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116682946A
Positive electrode material, positive plate and sodium ion battery
CN117080393A
Cited By
High-covalent-component sodium ferric pyrophosphate positive electrode material as well as preparation method and application of high-covalent-component sodium ferric pyrophosphate positive electrode material
CN119965262A
Carbon-coated sodium ferric phosphate positive electrode material, preparation method thereof and sodium ion battery
CN121672457A
Niobium-aluminum co-doped composite ferric sodium pyrophosphate material as well as preparation method and application thereof
CN122540833A